2019
DOI: 10.3151/jact.17.188
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependency of Short-Term Length-Change and Desorption Isotherms of Matured Hardened Cement

Abstract: Short-term length-change isotherms and desorption isotherms of matured hardened cement paste were measured at different temperature conditions, namely, 20, 30, 40, 50, and 60°C. For the short-term length-change isotherms, higher temperature conditions resulted in a smaller drying shrinkage. This trend was largely controlled by the microstructural reorganization of the calcium-silicate-hydrates in the cement paste at elevated temperatures. The experimental results suggest that a portion of the evaporable water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This discrepancy appears to be inappropriate. However, several reports have shown that the C-S-H packing density, interlayer spacing, and the microstructures change with temperature (Gallucci et al 2013;Bahafid et al 2017;Gajewicz-Jaromin et al 2019;Maruyama and Rymeš 2019). According to these studies, the interlayer spacing for specimens at 10°C is 35% larger than that at 60°C, and samples at 60°C were associated with increased pore size (capillary and interhydrate pores).…”
Section: Resultsmentioning
confidence: 97%
“…This discrepancy appears to be inappropriate. However, several reports have shown that the C-S-H packing density, interlayer spacing, and the microstructures change with temperature (Gallucci et al 2013;Bahafid et al 2017;Gajewicz-Jaromin et al 2019;Maruyama and Rymeš 2019). According to these studies, the interlayer spacing for specimens at 10°C is 35% larger than that at 60°C, and samples at 60°C were associated with increased pore size (capillary and interhydrate pores).…”
Section: Resultsmentioning
confidence: 97%
“…In the context of nuclear power plants, capturing the temperature dependency of this dynamic microstructure (related data has been reported by Maruyama and Rymeš (2019)) is critical for a more accurate estimation of the moisture transport, such as in a recent trial by Li and Xu (2019). To the authors' knowledge, no similar data for mid-range periods have been reported thus far.…”
Section: Introductionmentioning
confidence: 87%
“…Water movement in cement-based materials is dominated by the smallest pores with the smallest diffusivity and any variation in its microstructure will have important impacts on the apparent global transport coefficient. Under saturation conditions, the distribution of the pore sizes changes with the collapse of pores with time and many attempts to quantify this have been presented in previous studies (Gajewicz et al 2016;Zhou et al 2017Zhou et al , 2018Holthausen and Raupach 2018;Maruyama and Rymeš 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the irreversible shrinkage starts to form around 80% RH, but there is no direct experimental evidence. Temperature also has a strong influence on the shrinkage strain in this region (Maruyama and Rymeš 2019).…”
Section: Introductionmentioning
confidence: 93%